Therapeutic Effect of Portulaca oleracea‎‎‎ Against Diarrhea ‎Induced by Escherichia coli in Male Rats - M Manthoor, Ahmed; H Saliem, Ali (The Iraqi Journal of Veterinary Medicine, 2023)
This study aimed to investigate the in vivo antidiarrheal efficacy of methanolic extract ‎of Portulaca ‎oleracea against diarrhea induced by Escherichia coli in male rats. The initial ‎phase involved the ‎extraction of P. oleracea‎ using 99.8% absolute methanol through ‎a Soxhlet extraction apparatus. ‎Phytochemical analyses of the extract unveiled the presence ‎of alkaloids, flavonoids, steroids, ‎carbohydrates, tannins, and proteins. In the experimental ‎phase, 20 Wistar albino male rats (Rattus norvegicus) were divided into four ‎groups: the Negative Control ‎‎(uninfected and untreated); the Positive Control (infected but untreated); ‎POE group consisted of rats infected with E. coli‎‎ (1×109 CFU/mL) and subsequently treated ‎with 200 mg/kg BW of P. oleracea‎ methanolic extract orally ‎twice daily for seven ‎days; and CIP group included rats infected and treated with 7.14 mg/kg BW ‎of ‎ciprofloxacin orally twice daily for seven days. Outcome measures encompassed clinical ‎signs, ‎frequency of watery stools, rectal bacterial count, and changes in BW. ‎Remarkably, both POE and CIP groups demonstrated a statistically significant reduction in the ‎frequency of watery stools ‎‎(P<0.05) and a significant increase in BW (P<0.05) ‎compared to Positive Control group. Notably, there was ‎no significant difference in these parameters ‎between POE and CIP groups, suggesting that P. oleracea‎ ‎methanolic extract performs ‎comparably to ciprofloxacin in treating E. coli‎‎-induced diarrhea. The ‎findings illuminate ‎the potential of herbal medications such as P. oleracea‎ as effective alternatives to ‎antibiotics, ‎thereby mitigating the overuse of antibiotics and the associated risk of bacterial resistance.